NAATP response to National Treatment Plan. Issue 6 (7th February 2020) - Knopf, Alison
Abstract : After the release of the National Treatment Plan by the ONDCP, Mark Dunn, director of public policy for the National Association of Addiction Treatment Providers (NAATP), released the below statement.